Candidates Use Video Case Analysis to Examine Teacher Questioning Strategies. Issue 2 (3rd April 2021) - Hover, Ashlee
ABSTRACT: As part of the requirements for Residency I, a clinical-based course to prepare undergraduates for teaching, teacher candidates (art, music, physical education, agriculture, English, history, math, and science) participated in ATLAS video case analysis activities to examine the instructional strategies of accomplished teachers. Before watching the videos, candidates read lesson summaries and created possible questions to promote student discussion and higher-level thinking. Through peer group discussions, reflection questions, and interviews, candidates explained how the accomplished teachers 1) incorporated higher-order thinking questions; 2) probed and guided student thinking; 3) encouraged peer-to-peer interactions; 4) gave oral feedback; 5) provided wait time after questioning students; and 6) created classroom environments conducive to the use of questioning strategies. After the video case analysis activities, many candidates chose to revise their original questions to emulate the types of questions used by the accomplished teachers in the videos.